Consumer credit risk management - McNab, Helen; Taylor, Peter; IFS School of Finance (London, U.K. : Global Professional Publishing, 2008)
The book explores the history of credit scoring and analytics and the rationale behing the reliance on them. It also deals with the legal and regulatory regimes within which users must oprate, including Bank Code, the Business Banking Code, Treating Customers Fairly, Responsible Lending, the Competition Act 1998, the Data Protection Act 1984 and the Consumer Credit act 1974. Another area covered is key features of scorecard management and maintenance.
"A special edition of the IFS School of Finance text of Consumer credit risk management printed by Global Professional Publishing under license from IFS School of Finance"--P. [4] of cover.
Includes bibliographical references and index.
nmn 15/05/13
Loans
Keywords: Consumer credit; Risk management; Banks and banking